Patterns of honey storage in nests of the neotropical paper wasp Polistes simillimus Zikán, 1951 (Hymenoptera, Vespidae) - Prezoto, Fábio; Gobbi, Nivar [UNESP] (My University, 2003)
This study describes, for the first time, the occurrence of two patterns of honey storage in nests of the paper wasp Polistes simillimus. During the period of January of 1997 to September of 2000 we visited 262 colonies of P. simillimus, found at several places in States of São Paulo and Minas Gerais, in the southeast region of Brazil. Only in 2.67% of the colonies of P. simillimus searched presented the behavior of honey storage. Two of these colonies were in the pre-emergency phase, two in the post-emergency and three in decline. The results suggest that the honey storage can be correlated with the number of present individuals in the colony, because the colonies in decline, with larger number of individuals, presented many more cells occupied with honey than the nests in pre and post-emergency. There was not a pattern for the distribution of the cells with honey in the nests in decline. The honey storage in the colonies in pre and post-emergency of P. simillimus, suggests a strategy to increase success of foraging activity in the function of parental care. Already for the colonies in decline, this strategy seems to be associated with the individuals' survival in the aggregation, since the wasps are awaiting the passage of the unfavorable climatic conditions for the dispersion and foundation of new colonies.
Keywords: Behavior; Honey storage; Nests; Polistes simillimus; Vespidae; Hymenoptera; Polistes fuscatus pallipes